Review Article: Neospora caninum, A Neglected Parasitic Pathogen in Field Animals - Enas M.M. Al-Eodawee; Ola A. Aggar; Ghassan J.K. Al-Abedi (Zien Journals, 2023)
Neospora caninum represents one of most prevalent parasites in last three decades in many countries, worldwide. This parasite originates from canine species in particular dogs that act the definitive host to infect many domestic and wild animals that act as an intermediate host. These infections have revealed to cause different clinical symptoms among infected animals in dependence on the species of animal and the dose of ingested parasite. This leads to variable economic losses due to morbidities and mortalities, and cost of therapies and prevention. In Iraq, the main causes of abortion or even reduction in milk production or weight loss still unknown since most attempts of diagnosis based on the detectable clinical symptoms. Also, the number of carried out studies in dogs, cattle, sheep and goats remain low, and the available information are need to be supported. In addition, there is an obvious lack for governmental efforts to detect the actual prevalence of infection in herds or flocks and the role of other animals in transmission of infection through application of traditional or advanced diagnostic assays. Hence, the current study was aimed to clarify the main information concerned to N. caninum to list this parasite as one of the most important pathogens in field and its problematic role in field
Keywords: Neosporosis; Domestic animals; Dogs; Diagnosis